Innovative combined approach to the analysis of traditional media on the example of Georgia’s media space analysis («TV-Graph») - Lordkipanidze, Ana V.; Pachulia, Merab R.; Chuiko, Anna V. (Journal of the Belarusian State University. Sociology, 2019)
Television, on the one hand, is one of the main channels of information, and is very popular among viewers around the world, including Georgia, on the other hand, it is a source of data and a way of forming mass consciousness. That is why the research interest in the study of content and its impact on different groups of citizens is obvious. Most often, quantitative methods are used to analyze media content, the results of which reflect the preferences of viewers and the popularity of TV channels. The use of these methods does not allow to characterize the media content itself. This article proposes a method of combining quantitative and qualitative methods of analysis through sentiment analysis, the results of which allow to obtain non-trivial conclusions about the policy of TV channels and the ability to characterize the existing trends in society to form opinions on various issues. The methodology is tested on a specific empirical example («TV-Graph») of TV viewers in 7 cities of Georgia out of 540 households (approximately equal to 2000 individuals representing 1 572 000 Georgian population). The developments presented in this article are of particular interest to political and social scientists, as well as to all interested in this topic.